The Effect of Bowling Game on The Growth of 5-6 Years Old Children in Bidayatul Hidayah TK 2021 - Ismi Sudaryanti; I Made Suwasa Astawa; Ika Rachmayani; Baik Nilawati Astini (Jurnal Ilmiah Profesi Pendidikan, 2022)
This research is based on the importance of stimulation in six aspects of child development, namely physical development, motor, cognitive, language skills, social-emotional, artistic, as well as moral and religious values. One of the games that can stimulate children's growth and development is Bowling. Bowling is a type of sport or game that is played by rolling a ball using your hands. So the purpose of this study was to see the effect of Bowling on the growth and development of children aged 5-6 years in Bidayatul Hidayah Islamic Kindergarten with this type of experimental research using the One Group Pretest-Posttest Design method. The subjects of this study used 13 children aged 5-6 years in Bidayatul Hidayah Islamic Kindergarten. The data collection method in this research is observation and documentation. The data analysis technique was used between pretest and post-test with an error rate of 5%. Before the treatment, the average pretest average value increased post-test to 259.33. The results of the t-test is dk = N-1 = 13-1 = 12, and if the error rate is set at 5%, then = 2.179. The result of  is greater than  (24,639> 2,179). So Ha is accepted, and Ho is rejected. So it can be concluded that there is a significant influence on the application of bowling games on aspects of the growth and development of children aged 5-6 years in Bidayatul Hidayah Islamic Kindergarten in the 2020 Academic Year so that bowling games can be used as an alternative in developing the growth and development abilities of children aged 5-6 years.